Rancangan Sumur Resapan pada Bangunan Hunian Vertikal sebagai Implementasi kriteria Greenbuilding - Manik, Ayu Sartika Imia; Saptomo, Satyanto Krido; Chadirin, Yudi (Departemen Teknik Sipil dan Lingkungan, IPB University and The Institut of ENgineering Indonesia (PII), Bogor, 2024)
Land-use change due to development continues to increase so that it impacts decreasing infiltration area and increasing surface water runoff. One of the solutions to merahuce runoff is to apply green building concepts using infiltration wells. This study aims to design infiltration wells based on greenship new building 1.2 to merahuce the volume of rainwater runoff and STP runoff water that has met the quality standards at vertical residential buildings, as well as assessing the green building category of land use at design recognition stage. The results of planning rainwater absorption wells in accordance with the greenship new building version 1.2 showed that it is necessary to make circular infiltration wells with a diameter of 1,5 m and a depth of 5 m. It takes as many as 34 units with an effectiveness value of 99.1%. While the infiltration well for STP effluent water is required as many as 44 units with 100% effectiveness. The result of green building assessment in this apartment plan for appropiate site development category has reached 64% (11 out of 17 points)